2017
DOI: 10.1108/jica-09-2016-0034
|View full text |Cite
|
Sign up to set email alerts
|

An electronic referral system supporting integrated hospital discharge

Abstract: Purpose The purpose of this paper is to evaluate the implementation and potential value of an electronic referral system to improve integrated discharge planning for hospitalised older adults with complex care needs. This new technology formed part of the “Common Assessment Framework for Adults” policy in England. Design/methodology/approach Mixed methods were undertaken as part of a case study approach within an acute hospital in the North West of England. First, qualitative interviews were undertaken with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(48 citation statements)
references
References 11 publications
(19 reference statements)
0
48
0
Order By: Relevance
“…Contrastingly, Wilberforce et al 23 reported that 21 per cent of e-handover documents contained incomplete fields versus 13 per cent of paper documents ( p = 0.039). 23…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Contrastingly, Wilberforce et al 23 reported that 21 per cent of e-handover documents contained incomplete fields versus 13 per cent of paper documents ( p = 0.039). 23…”
Section: Resultsmentioning
confidence: 88%
“…Wilberforce et al, 23 the only study to demonstrate a reduction in handover completeness post-implementation failed to describe if their e-handover platform had the same number of fields as the paper documentation or how they selected handovers to audit. It is therefore unclear if their findings are a result of selection bias or a genuine reduction in completed handovers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is perhaps a consequence of health and social care practitioners being in separate locations and lacking the opportunity for and benefits of informal corridor conversations (González-Martínez et al, 2015). Other research conducted in a district general hospital within the same demonstration programme demonstrated that face-to-face transfer of information was preferable to electronic transfer between ward staff and discharge coordinators (Wilberforce et al, 2017). Van der Meiden and colleagues (2003) suggested that the successful implementation of a computer-based information system was a relative concept, perceptions of which may change over time.…”
Section: Discussionmentioning
confidence: 99%